BAPERKI sebagai Politik Identitas dan Representasi Masyarakat Tionghoa di Indonesia - Ahmad Bakhtiar; Nurbaity Nurbaity; Yusuf Budi Prasetya Santosa (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
The history of the Chinese diaspora to Indonesia is very interesting to discuss. The long process of the arrival of the Chinese community to Indonesia long before the arrival of westerners to Indonesia has formed a separate identity for the Chinese community who in the end had to accept the policy of 'assimilation'. This process is part of the representation of the Chinese community in Indonesia. The Chinese themselves feel that they are different from the natives in all respects, so the feeling of being a minority group is getting stronger. The Chinese increasingly showed their cultural identity after the construction of various facilities such as a special school for the Chinese, a Chinese cultural group, and a Chinese-language newspaper. In order to accommodate these interests and due to the pressure and atmosphere at that time, in 1954 the Indonesian Citizenship Consultative Body (BAPERKI) was formed. This study uses the historical method to explain the role of BAPERKI as a political identity and representation of the Chinese community in Indonesia. The stages that are passed are the heuristic stage (data collection), the critical stage, the interpretation stage and the historiography (historical writing). The increasing role of the Chinese community in Indonesia has caused them to form organizations that can protect their people, who indeed have a minority number. For that purpose, they formed BAPERKI. BAPERKI has a role as a socio-political organization of the Peranakan Chinese group in Indonesia. The issue of citizenship is the background behind the establishment of BAPERKI.